2008
DOI: 10.1007/s11010-008-9722-8
|View full text |Cite
|
Sign up to set email alerts
|

Chemoresistance in gliomas

Abstract: Despite improved knowledge and advanced treatments of gliomas, the overall survival rate for glioma patients remains low. Gliomas comprise of significant cell heterogeneity that contains a large number of multidrug resistant (MDR) phenotypes and cancer stem cells (CSCs), a combination that may contribute to the resistance to treatment. This article reviews the MDR related genes, major-vault protein (MVP), anti-apoptotic protein (Bcl-2) and the molecular mechanisms that may contribute to chemoresistance, in add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(103 citation statements)
references
References 85 publications
2
101
0
Order By: Relevance
“…However, the potential contribution of microglia produced NO to the tumor stem cell phenotype that has yet to be explored. It has also been shown that glioma stem-like cells express multi-drug resistance proteins such as ABCG2 and P-gp (Lu and Shervington, 2008;Bleau et al, 2009;Wang et al, 2010); hence, these cells tend to be highly resistant to cytotoxic drug therapy (Charles and Holland, 2009 (Dix et al, 1999). Signaling through CXCL12-CXCR4 is known to recruit Tregs to bone marrow and may also be involved in the recruitment of Tregs to brain tumors (Zhou et al, 2002;Grauer et al, 2007).…”
Section: Glioma Stem-like Cellsmentioning
confidence: 99%
“…However, the potential contribution of microglia produced NO to the tumor stem cell phenotype that has yet to be explored. It has also been shown that glioma stem-like cells express multi-drug resistance proteins such as ABCG2 and P-gp (Lu and Shervington, 2008;Bleau et al, 2009;Wang et al, 2010); hence, these cells tend to be highly resistant to cytotoxic drug therapy (Charles and Holland, 2009 (Dix et al, 1999). Signaling through CXCL12-CXCR4 is known to recruit Tregs to bone marrow and may also be involved in the recruitment of Tregs to brain tumors (Zhou et al, 2002;Grauer et al, 2007).…”
Section: Glioma Stem-like Cellsmentioning
confidence: 99%
“…Another feature that normal stem cells and glioma stem cells share is expression of drug efflux pumps. Adenosine triphosphate-binding cassette (ABC) pumps, ABCG2 and Pglycoprotein are expressed on glioma stem cells and are responsible for efflux of the fluorescent Hoechst 33342 dye, leading to the side population, which is enriched in glioma stem cells (Lu and Shervington, 2008). However, in a model system, ABCG2-positive andnegative cells showed no difference in tumor formation in mice (Patrawala et al, 2005).…”
Section: Chemoresistance and Radioresistancementioning
confidence: 99%
“…BCRP1 is a member of the ATP binding cassette (ABC) transporters comprising of 48 members. 97 These transporters traffic molecules such as lipids and xenobiotic compounds across the cell membrane in an ATP dependent mechanism 97 . Another gene is MGMT, which is required to repair O 6 -methylguanine DNA induced damage by drugs such as temozolomide.…”
Section: Responses To Chemotherapy Drugsmentioning
confidence: 99%